Application of Remote Sensing for Estimation of Carbon Storage in a Plantation Forest on Reclaimed Land of Banpu Lignite Mine and Adjacent Natural Forest, Northern Thailand - Thiteja, Suppagarn; Khamyong, Soontorn; Charoenpanyanet, Arisara; Huttago, Panlop; Boontun, Amarin (International Journal of Engineering and Technology, 2018)
The carbon storage assessment of a 18-year-old plantation forest (PF) on reclaimed land of Banpu lignite mine, northern Thailand, was compared to nearby natural forest (NF), the dry dipterocarp forest (DDF). Vegetation study was taken using the sampling plot, each of size 40×40 m, and the total number of 12 and 10 plots were used for the PF and the NF, respectively. Data were obtained by measuring stem girths at breast height (1.3 m above ground, gbh) and heights of all trees with height over 1.5 m. The standing biomass and stored carbon amounts were calculated using allometric equations. The relationship between the carbon storage (CS) with actual wavelength associated with the vegetation was taken. LANDSAT-8 OLI images captured in 2015 were used for correlation and the multiple regression analysis for selection of the best equation to estimate the CS. It is found that the total number of 47 species (38 genera, 20 families) and 98 species (85 genera, 45 families) were existed in the PF and the NF, respectively. The CS amounts in plant biomass of the PF and the NF were determined in the following order; 47.80 ± 9.24 Mg ha-1 and 64.39 ± 13.7 Mg ha-1. The best-fit model for estimation of the CS in study plots showed the relationship between the ratio vegetation index (RVI) and the normalized difference vegetation index (NDVI); the PF, CS = (3467NDVI) - (743RVI) + 392 with R2 = 0.96, and the NF, CS = (217RVI) - (542NDVI) - 194 with a coefficient of determination (R2) of 0.79. The average CS amounts of the NF and the PF by remote sensing assessment were estimated at 63.54 Mg ha-1 and 41.60 Mg ha-1, respectively. The CS estimation of the PF was lower than the NF. Improving planting technique is required for forest plantation on the reclaimed mine land to increase plant species diversity, biomass and carbon storages.